Hábitos de consumo de álcool em estudantes do ensino superior universitário: alguns dados empíricos - Martins, Jorge Simões (2010)
This study aimed to provide a brief overview of the drinking habits and alcohol-related consequences in a sample of university students. The sample included 654 students who were given the Alcohol Use Disorders Identification Test (AUDIT), the Brief Young Adult Alcohol Consequences Questionnaire (B-YAACQ) and the Daily Drinking Questionnaire – Revised (DDQ-R). Special attention was devoted to the patterns of alcohol use as well as to prevalence rates of alcohol-related consequences. The results provide further support for the need to develop early preventive strategies which are more adjusted to the different students’ profiles, that is, to the characteristics of developmental stage and specific necessities of those students. Considering these characteristics and needs will certainly clarify the professionals and therefore promote the effectiveness of the intervention.